(untitled) (Jurnal Ekonomi dan Manajemen, 2024)
The purpose of this study is to analyze the impact of communication and organizational commitment on the performance of the community in the Mojokerto Regional Government Secretariat. Methodology: the population in this study is an employee of the Mojokerto Regional Government Secretariat and this research is quantitative with a research instrument in the form of a questionnaire which is then analyzed using the help of the SPSS Version 22 program. Results: direct communication has a significant effect on organizational commitment in the Regional Secretariat of Mojokerto Regency; Direct supervision has a significant effect on organizational commitment, communication directly has a significant effect on employee performance, direct supervision has a significant effect on employee performance, that organizational commitment directly has a significant effect on employee performance, communication indirectly affects employee performance through organizational commitment, that supervision indirectly affects employee performance through organizational commitment at the Regional Secretariat of Mojokerto Regional Government.